Effects of Shadowing on LoRa LPWAN Radio Links - Mohamed Hadi Habaebi; Israth Jahan Chowdhury; Md Rafiqul Islam; Nur Aishah Binti Zainal (International Journal of Electrical and Computer Engineering (IJECE), 2017)
LoRaWAN is a long-range, low-power, wireless telecommunications method; expected to play a big role for the Internet of Things. End appliances use LoRaWAN through a single wireless hop to communicate with gateways linked to the Internet that function as transparent bridges relaying messages amongst these end-devices and a central network server. This technology youtes a combination of extended range, low power utilization and protected data communication and is gaining significant traction in IoT networks being deployed by wireless network operators. However, no comprehensive evaluation of the technology exists in the open literature. The main intention of this paper is to investigate the effects of shadowing on LoRaWAN links and analyze the performance in terms of packet loss ratio for different physical layer settings. Results indicate large differences in performance when shadowing is taken into consideration upsetting the expected performance tremendously.